KESIAPAN HAKIM PENGADILAN AGAMA DI MADURA DALAM MENYELESAIKAN SENGKETA EKONOMI SYARI’AH - Shofiyun Nahidloh (Universitas Trunojoyo Madura, 2018)
Public assumes that knowledge of the judge of religious court is moreconcentrated in marital disputes, inheritance, wills, grants, waqaf and sadaqah that be handled, rather than knowledge of sharia economy. Seeing the judge had received his various background of education levels and the representative office building conditions of the religious court, so that it would have been more ready to hear the case of economic disputes than general court. But in Madura, it does not appear yet to have a significant progress as the impact of the regulatory changes, contained in the constitution, number 7 of 1989 jo. number 3 of 2006 on the Religious Court, where there are some additional authorities to resolve some disputes in the field of shariah economic matters.Publik mengasumsikan pengetahuan hakim pengadilan agama lebih tertumpu di bidang sengketa perkawinan, waris, wasiat, hibah, waqaf dan sedekah yang ditanganinya, ketimbang pengetahuan ekonomi syariah itu sendiri. Melihat hakim telah mengenyam berbagai latar belakang jenjang pendidikan dan kondisi gedung kantor pengadilan agama yang representatif, maka pengadilan agama tentu telah dan lebih siap mengadili perkara sengketa ekonomi syariah ketimbangan pengadilan dalam lingkungan peradilan umum. Namun di wilayah Madura belum nampak adanya progress yang signifikan dari dampak adanya perubahan regulasi yang tertuang dalam dalam UU No.7 Tahun 1989 jo.UU No.3 Tahun 2006 tentang Peradilan Agama dimana ada tambahan kewenangan yaitu menyelesaikan sengketa di bidang perkara ekonomi syari’ah.Keywords: Judge PA, Dispute, Economic sharia, Madura